KOMPARASI HASIL BELAJAR ANTARA STRATEGI PREDICT-DISCUSS-EXPLAIN-OBSERVE-DISCUSS-EXPLAIN (PDEODE) BERBASIS LABORATORIUM DAN BERBASIS MULTIMEDIA PADA PEMBELAJARAN KELARUTAN DAN HASIL KALI KELARUTAN - Anang Budianto; Syahmani Syahmani; Maya Istyadji (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. Effectiveness between PDEODE based multimedia, PDEODE based laboratory and expository instructional strategy to improve learning outcome has been investigated. This study was used quasiexperiment with pretest-posttest nonequivalent group design. Next to that, the study involved students of class XI SMAN 2 Banjarmasin as research subject. The instrument that was used to compare student’s learning outcome of three classes is cognitive test with multiple choice form. Data was analyzed by one way Anova and Duncan. Based on analyze, this study showed that (1) there is a significant difference of learning outcome between PDEODE based multimedia, PDEODE based laboratory and expository instructional strategy (2) the use of PDEODE based multimedia is more effective than the use of expository or PDEODE based laboratory.